Design Thinking "The Urgency of Maintaining Environmental Cleanliness" was the inspiration of the Prophet - Apriliandi Yaasin; Deni Miharja (Gunung Djati Conference Series, 2021)
This study aims to discuss the inspiration of the hadith in maintaining cleanliness. This research method is qualitative through the study of hadith. The results and discussion of this study include the application of maintaining environmental cleanliness, the inspiration of the Prophet's example in maintaining environmental cleanliness, and effective ways of keeping the environment clean. Research with a design thinking approach concludes that the Prophet's hadith have inspiring messages in keeping the environment clean so that humans can avoid various diseases so that a clean environment is created.